Sola gratia: der Streit um die Gnade im 16. Jahrhundert, seine Auswirkungen für die Neuzeit und seine Virulenz in der Gegenwart - Ruhstorfer, Karlheinz (Zeitschrift für katholische Theologie, 2004)
The "Common declaration about the theology of justification" from 1999 contains a "differentiated consensus". To understand the differences one must have recourse to the catholic position based on the thinking of late Antiquity and the Middle Ages as well as the protestant position grounded in modern thinking. The article exemplifies this hypothesis with an analysis of the relationship between grace and freedom in the thought of Thomas Aquinas, Martin Luther, Luis de Molina, and Immanuel Kant. Ecumenical progress depends to a great extent on the ability to relate medieval and modern thought.